Expenditure Conditionality in IMF-supported Programs - Gupta, Sanjeev (IMF Working Papers; Working Paper, 2018)
This paper studies the impact of expenditure conditionality in IMF programs on the composition of public spending. A granular dataset on different government expenditure conditions covering 115 countries for the 1992-2016 period is compiled. The results support the view that while conditionality on specific elements of spending could help achieve a program's short-term objectives, it is structural conditionality which delivers lasting benefits. Structural public financial management conditionality (such as on budget execution and control) has proven to be effective in boosting the long-term level of education, health, and public investment expenditures. The results further indicate that conditionality on raising such spending may come at the expense of other expenditures. Finally, the successful implementation (and not mere existence) of the conditionality is crucial for improved outcomes. These findings are relevant for policy makers targeting achievement of the Sustainable Development Goals (SDGs).